The impact of coping strategies on the intensity of stress on hemato-oncology nurses - Juliane Umann; Rodrigo Marques da Silva; Sonia Betzabeth Ticona Benavente; Laura de Azevedo Guido
We intended to evaluate the impact of coping strategies on the intensity of stress on hemato-oncology nurses, using a transversal analytical study conducted with 18 nurses between March and April of 2010. We used a form for socio-demographic characterization, the Occupational Coping Scale to evaluate the coping strategies and the Nurses Stress Inventory to evaluate the stress. There was no significant correlation between coping strategies and stress intensity, however, in the dispersion analysis, the use of control and avoidance strategies increased stress intensity while the use of symptoms management decreased its intensity. Nurses with less time working in the health institution and those without a postgraduate degree presented higher stress intensity. We concluded that Symptoms Management strategy has a positive effect on the stress of hemato-oncological nurses, where the reduced perspective of healing and the chronic condition of the patients are inherent to the nursing work and make proactive and avoidance actions difficult.